Omega-3 fatty acids abrogates oxido-inflammatory and mitochondrial dysfunction-associated apoptotic responses in testis of tamoxifen-treated rats - Odetayo, Adeyemi Fatai; Akhigbe, Roland Eghoghosoa; Hamed, Moses Agbomhere; Balogun, Morufu Eyitayo; Oluwole, David Tolulope; Olayaki, Luqman Aribidesi (Frontiers in Nutrition, 2024)
BACKGROUND: Tamoxifen (TAM) is a widely used drug in patients with gynecomastia and breast cancer. TAM exerts its anticancer effects via its antiestrogenic activities. Unfortunately, TAM has been reported to exert gonadotoxic effects on male testes. Therefore, this study was designed to explore the possible associated mechanisms involved in TAM-induced testicular dysfunction and the possible ameliorative effects of omega-3 fatty acids (O3FA). METHODOLOGY: Animals were randomly divided into control, O3FA, TAM, and TAM + O3FA. All treatment lasted for 28 days. RESULTS: TAM exposure impaired sperm qualities (count, motility, and normal morphology) and decreased testicular 3β-HSD and 17β-HSD. It was accompanied by a decline in serum testosterone and an increase in estradiol, luteinizing and follicle-stimulating hormones.These observed alterations were associated with an increase in testicular injury markers, oxidoinflammatory response, and mitochondria-mediated apoptosis. These observed alterations were ameliorated by O3FA treatments. CONCLUSIONS: O3FA ameliorated TAM-induced testicular dysfunction in male Wistar rats by modulating XO/UA and Nrf2/NF-kb signaling and cytochrome c-mediated apoptosis in TAM-treated rats.